My Windows 8.1 - Murray, Katherine, 1961- (Que, 2014)
"Step-by-step instructions with callouts to Windows 8.1 photos that show you exactly what to do. Help when you run into Windows 8.1 problems or limitations. Tips and notes to help you get the most from your Windows 8.1 computer."--Back cover.